Urbanization, Migration, Information - Lidin, Konstantin (project baikal, 2016)
In the contemporary world urbanization becomes a large-scale process. Huge flows of people migrate from poorer districts to the cities with a higher level of consumption. It takes migrants about 15-25 years to give up their traditional ascetic way of life. In this period the ‘new citizens’ try to arrange compact settlements with an archaic way of life, insanitary conditions, high criminogenity and an authoritative local self-government. The processes of formation and decay of the ascetic enclave are viewed through the example of the ‘Shanghai’ trading neighborhood in Irkutsk.